Concurrence of Congenital Muscular Torticollis and Congenital Torticollis Due to Other Anomalies: Two Case Reports - Kim, Min-Wook; Kim, Da-Ye; Lee, Dong-Woo; Ryoo, Da-Hye; Kim, Jaewon; Jang, Dae-Hyun (Frontiers in Pediatrics, 2021)
Introduction: Congenital muscular torticollis (CMT) is the most common cause of torticollis in infants; other causes, including osseous, ocular, and central nervous system torticollis can easily be overlooked. We report two rare cases of CMT with concurrent osseous or ocular torticollis. Case 1: A 1-month-old female infant with a right neck mass and right-tilting head posture was referred. Neck ultrasonography showed diffuse hypertrophy and hyperechoic findings on the right sternocleidomastoid (SCM) muscle, which was consistent with right CMT. A clavicle X-ray imaging was conducted to identify an associated fracture due to birth trauma on the same day and a suspected congenital vertebral anomaly was coincidentally found. Subsequent three-dimensional computed tomography of the cervical spine showed a T1 hemivertebra causing the right-tilting head. The patient was diagnosed with the concurrent manifestation of CMT and congenital osseous torticollis. Case 2: A 3-month-old male infant with a 20° head tilt to the right with a limited cervical range of motion was referred. Neck ultrasonography showed a fibromatosis colli in the right SCM, suggesting CMT. He proceeded to physical therapy for seven months; however, there was little clinical improvement in his head and neck posture. The patient underwent an additional ophthalmologic examination and orbital magnetic resonance imaging (MRI) at 10 months of age. The result showed congenital agenesis of the left fourth cranial nerve with hypoplasia of the superior oblique muscle causing the right-tilting of the head. Ultimately, the boy was diagnosed with a concurrent manifestation of CMT and congenital ocular torticollis. Conclusion: Unless careful examinations are conducted, congenital vertebral anomalies and congenital agenesis of the fourth cranial nerve can go unnoticed in the present two cases. If a patient with CMT displays unusual features or does not respond to physical therapy, clinicians should consider not only a differential diagnosis but also concurrence with other causes of congenital torticollis.